2014
DOI: 10.1080/15567249.2010.527900
|View full text |Cite
|
Sign up to set email alerts
|

An Efficiency Evaluation of the EU’s Allocation of Carbon Emission Allowances

Abstract: The allocation of carbon dioxide emission allowances has become one of the most important global issues. The main argument is the equity in the allocation of emission allowances. If the allocation is unfair, then economic development of some countries will be impeded. Therefore, to promote an emissions trading system, an equitable and reasonable allocation method that benefits every participant country is needed, so that countries will accept and implement the system accordingly.This study uses emission allowa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Many studies have indicated a single-direction causal relationship between GDP and CO 2 [25][26][27]. Dinda [28] indicated that there is a two-directional relationship between economic development and environmental pollution.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have indicated a single-direction causal relationship between GDP and CO 2 [25][26][27]. Dinda [28] indicated that there is a two-directional relationship between economic development and environmental pollution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although energy is highly relevant to national security, a degree of privatization can mitigate the bureaucracy typically seen in state-owned enterprises, and enhance the efficiency of market competition through transmission and distribution; moreover, privatization attracts foreign investment and introduces state-of-the-art technologies in energy efficiency. Italy is expected to phase out subsidies and incentives to high energy-consuming industries, and its government encourages the development of carbon emission technologies and improved energy efficiency [25]. Table 2 also summarizes the MTRs in Asia during the research period.…”
Section: Empirical Analysismentioning
confidence: 99%
“…At present, most of the international greenhouse gas emission regional decomposition schemes are aimed at the allocation among countries [26], because it is the core issue of the Kyoto protocol. Using the experience of other principles and methods for decomposition method for reference, some scholars have been carrying out the relevant regional decomposition models [27,28], these research results have important reference significance to our study about regional-level CO 2 emission permits allocation.…”
Section: The Choice Of Permits Allocation Methods Among Regionsmentioning
confidence: 99%
“…Gomes [31] developed the zero-sum game DEA (ZSG-DEA) model, taking CO 2 as the input variable allocated among Kyoto Protocol Contracting Parties-ZSG-DEA was proven to realize technical efficiency for all DMUs after optimization by multiplying an allocation coefficient. Other researchers applied ZSG-DEA, including Serro [32], Wang et al [33], Pang et al [34], and Chiu et al [35], and provided valuable findings; Lozano et al [36] used the centralized reallocation DEA model for emissions allocation. Notable studies on the centralized DEA model were conducted by Wu et al [37], Singh and Majumdar [38], Sun et al [39], Homayounfar et al [40], and Feng et al [41].…”
Section: Literature Reviewmentioning
confidence: 99%